Foeto-foetal transfusion syndrome in dichorionic diamniotic twins: a clinical case - E. K. Gordeeva; A. V. Pomortsev; I. B. Vasina; M. A. Asriants; T. A. Sadovnikova (Кубанский научный медицинский вестник, 2021)
Background. Management of multiple gestation complicated by the foeto-foetal transfusion syndrome is among most intricate modern obstetric issues. The syndrome develops in 10–20% of monochorionic diamniotic twins leading to 80–100% mortality in one or both twins if left uncorrected, especially in early syndrome cases. Although foeto-foetal transfusion usually develops with monochorionic placentae, there are notable exceptions of vascular placental anastomoses reported with dichorionic monozygotic twins. The disease supposedly entails from an imbalanced blood interflow between dichorionic twins due to placental vascular anastomoses.Clinical Case Description. Patient S., 32 yo, visited perinatal diagnostics at the Territorial Perinatal Centre of the Children’s Territorial Clinical Hospital with a preliminary diagnosis: 22 weeks and 5 days’ pregnancy. Dichorionic diamniotic twins. Threat of extremely preterm birth. Two caesarean uterine scars. Gestational diabetes mellitus.Medical files: patient history, pregnancy calendar. Pregnancy was regularly monitored with main ultrasound foetometry, foeto-foetal transfusion dynamics control and Doppler velocimetry.Ultrasonographic signs of abnormal haemodynamics underlying the foeto-foetal transfusion syndrome were detected at the first scan at 11–13 weeks 6 days’ term as collar space thickening in one foetus. Hydramnios in one foetus and oligohydramnios in the other were diagnosed at 28 weeks’ gestation conclusively indicating the foeto-foetal transfusion syndrome. This evidence suggested the formation of placental anastomoses, which was confirmed morphologically in placenta examination.Conclusion. A timely diagnosis and correction of emerging complications allowed prolongation of pregnancy in hospital conditions to 33–34 weeks. Both boys were live-born with Apgar score 7–8.